Pseudocholinesterase, aspartate transaminase, alanine transaminase as markers for cervical cancer: a study in a tertiary care hospital - Veeramalla, Vydehi (International Journal of Advances in Medicine, 2017)
Background: Cervical cancer is a malignant neoplasm arising from cells originating in the cervix, almost always caused by human papillomavirus (HPV). Butyrylcholinesterase is a non-specific cholinesterase enzyme that hydrolyses different choline esters. PCHE levels were lower than the normal at all the stages of cancer cervix. The present study was attempted to find out the role of some of the biochemical markers like serum pseudocholinesterase (PCHE), serum aspartate transaminase (AST), and serum alanine transaminase (ALT), in malignancy of the uterine cervix. Methods: 60 patients aged between 30 -70 years who were having cervical cancer were included into the study and 30 healthy patients within the same age group were included as controls. 5ml of venous blood was collected from all the study participants under aseptic conditions in a plain tube. Serum Pseudocholinesterase, Serum Aspartate transaminase and Serum Alanine transaminase was estimated for all the patients in both the groups. Results: The mean value of pseudocholinesterase in cervical cancer patients was lower in the cases when compared to controls and it was statistically significant (P value 0.0005), while the mean value of serum AST and ALT were higher in cases when compared to controls and it were also statistically significant. When compared with Pearson’s coefficient, the serum PChE had a significant negative correlation with AST and ALT, while the serum AST had a significant positive correlation with ALT and a negative correlation with PChE. Conclusions: Among the women with cervical cancer, it was observed that the enzyme activity of PChE was lower than normal, while that of SGPT and SGOT were higher. PCHE, AST, and ALT can be used as tumor markers in the management of malignancy of the uterine cervix.